Working hours, work identity and subjective wellbeing - Mark Bryan; Alita Nandi (University of Essex, Institute for Social and Economic Research (ISER), 2015)
Following theories of social and economic identity, we use representative data containing measures of personal identity to investigate the interplay of work identity and hours of work in determining subjective wellbeing (job satisfaction, job-related anxiety and depression, and life satisfaction). We find that for a given level of hours, having a stronger work identity is associated with higher wellbeing on most measures. Working long hours is associated with lower wellbeing and working part-time is associated with higher wellbeing, but for men hours mainly affect their job-related anxiety and depression rather than reported satisfaction. The relationships between hours and wellbeing are generally strengthened when controlling for identity implying that individuals sort into jobs with work hours that match their identities. Work identity partially mitigates the adverse effects of long hours working on job satisfaction and anxiety (for women) and on life satisfaction (for men). The effects of both work hours and identity are substantial relative to benchmark effects of health on wellbeing.
Keywords: J22; J28; J29; I31; 330; identity; wellbeing; working hours; job satisfaction; anxiety; depression